Non-tuberculous Mycobacterial Infection (Mycobacterium Abscessus) after Anterior Cruciate Ligament Reconstruction: A case report - Umprai, MD, Vantawat; Yuktanadana, MD, Pongsak (Journal of Southeast Asian Orthopaedics, 2022)
Infection after anterior cruciate ligament (ACL) reconstruction is an uncommon condition. We report a case of non-tuberculous infection (Mycobacterium Abscessus) after ACL reconstruction with an autologous quadruple hamstring graft and fixation with a bioabsorbable interference screw. One year after arthroscopic ACL reconstruction surgery, the patient presented with a painless posterolateral mass of the knee. The patient underwent open debridement of the abscess at the posterolateral aspect of the knee. The tissue culture after 6 weeks from the first surgery was positive for Mycobacterium abscessus, proper antibiotic treatment was given by the infectious specialist. Abscess and drainage recurred 3 months after first debridement, another open debridement was done and antibiotic was given for another three months. At the last follow up at King Chulalongkorn Memorial hospital, the wound was closed and the patient was symptom free. To our knowledge, this is the first preliminary case report of a non-tuberculous (M. abscessus) infection after ACL reconstruction.